A comparative study on shells in Linux: A review. (2021) - Kidwai, Abdullah; Arya, Chandrakala; Singh, Prabhishek; Diwakar, Manoj; Singh, Shilpi; Sharma, Kanika; Kumar, Neeraj
Abstract: The purpose of the study is to find the best shells available in Linux Operating System. The study has been narrowed down to seven most prominent shells in use today. With so many different Linux distributions and a plethora of shells, there exists a problem of plenty, which is rather a good problem to have. Amid all this confusion, one wonders which shell to use. Which is most suitable to one's requirement, is modern, up to date and provides all sort of features which fulfils the desire of the user as well as the developer. The article deals in brief about Linux and its distributions, its philosophy and the freedom it provides. Shells, its scripting and shell types have been explained, one gets an idea of the study from the introduction. The seven Linux shells have been explained in detail to familiarize the reader with the most popular and most used shells available. A clear, concise and comparative analysis of the shells based on their general, interactive, programming and security features has been given. Programming features are important for the developers while a good interface makes everyone happy. Security features are a must for anyone who values their privacy and would like no intrusion in their system or their files. The mechanism of communication is important for I/O handling, as well as managing, interrupts. The speed of the system is greatly affected by the level of efficiency of inter-process communication.